THU0033 Effects of Early Remission on Work Ability and Absenteeism in Early Rheumatoid Arthritis. (15th July 2016) - Cheng, T.H.; Kwok, K.Y.; Tam, L.-S.; ,
Abstract : Background: Treatment of RA is increasingly aimed at remission. A small scale study on patients who were clinically regarded to be in remission felt that they were able to continue their normal everyday activities at home, at leisure and at work (1). However, whether achieving early disease remission by tight control treatment can predict improvement in work ability remained uncertain. Objectives: To ascertain whether achieving early remission will influence work ability and absenteeism in early RA patients treated by a protocol-driven, tight-control strategy after 1 year. Methods: Early RA patients with symptom onset of less than 2 years were recruited for this prospective cohort study. All patients were treated according to a tight control protocol aiming at remission. Early remission was defined as achieving Disease Activity Score (DAS) or Simplified Disease Activity Index (SDAI) remission after treatment for 3 months. Work ability was assessed by the self-perceived working ability index (WAI) compared to life time best (score from 0–10, with 10 as best). WAI was evaluated at both baseline and 1 year after treatment. The days of sick leave were also retrieved. Logistic or linear regression models were used to assess baseline clinical and demographic predictors, with the need to take sick leave and month 12 WAI during the 1-year period following RA diagnosis as outcome. Results: 103 early RA patients (79 female and 24 male, mean age: 55.7±13.1 years) completed 1 year follow-up. At baseline, the mean baseline WAI was 4.97±2.9. 12/103 patients (12%) were unable to work as a result of the disease. After treatment for 3 months, 38 (36.9%) achieved DAS remission and 18 (17.5%) achieved SDAI remission. After treatment for 1 year, the WAI increased significantly to 6.45±2.6 ( p <0.001) and 6/12 (50%) were able to go back to the work force again. Using univariate analysis, the baseline physician global assessment score (PhyGA), patient global assessment score (PatGA), tender joint count, swollen joint count, DAS-ESR, DAS-CRP, SDAI and HAQ were negatively associated with month 12 WAI. Early DAS remission ( r =0.233, p =0.018) and SDAI remission ( r =0.336, p =0.001) were positively associated with month 12 WAI. Using multivariate linear regression, early SDAI remission (β=2.256, 95% CI: 0.945–3.566, p =0.001) was an independent predictor for higher month 12 WAI after adjustment for the baseline characteristics. The working population (n=65, 15 achieved early SDAI remission and 29 achieved early DAS remission) was further analyzed. Significantly less patient required sick leave ≥1 day(s) if early SDAI remission was achieved [3 (20.0%) vs 12 (80%), p =0.010] but not DAS remission [12 (41.4%) vs 17 (58.6%), p=0.256]. Using univariate logistic regression, baseline PhyGA, DAS-CRP, WAI, HAQ, SF36 Physical component score were associated with ≥1 day(s) of sick leave, while patients not achieving early SDAI remission (OR=5.524, 95%CI:1.384–22.049, p =0.016) was more likely to require any sick leave. Using multivariate logistic regression, not achieving early SDAI remission was the independent predictor for taking sick leave (5.317, 1.314–21.516, p =0.019). Conclusions: Early RA patients who achieved early SDAI remission had better self-perceived working ability and were less likely to require sick leave after adjustment of baseline characteristics. References: Kristiansen TM et al., Musculoskeletal Care. 2012;10:162–70. Disclosure of Interest: None declared